(untitled) (International Journal of Engineering and Computer Science, 2024)
Digital twins, defined as virtual replicas of physical entities, are emerging as transformative tools in IT systems, bridging the gap between physical infrastructure and digital insights. This paper delves into their critical applications in real-time system monitoring, emphasizing their role in optimizing performance, enabling predictive maintenance, and enhancing cybersecurity. By creating dynamic models that simulate system behaviors and operational states, digital twins empower IT managers to make informed decisions with unparalleled precision. The paper outlines key applications, including real-time performance monitoring, where digital twins analyze live data to optimize IT infrastructure efficiency. Predictive maintenance applications are explored, demonstrating how twins preemptively identify potential failures, reducing downtime and operational costs. Additionally, their utility in cybersecurity is highlighted, where digital twins detect and mitigate anomalies, safeguarding critical systems against cyber threats. However, the integration of digital twins into IT systems is not without challenges. These include the complexities of managing vast amounts of real-time data, ensuring scalability across diverse IT environments, and addressing compatibility issues with legacy systems. Furthermore, real-time processing demands and concerns over data security and privacy are significant barriers to widespread adoption. To address these challenges, the paper proposes solutions such as leveraging edge computing and AI for low-latency analytics, adopting standardized frameworks to enhance interoperability, and implementing advanced cybersecurity measures to protect sensitive data. Current best practices in deploying digital twins are also discussed, providing actionable insights for IT professionals. The paper concludes by exploring future research directions, including hybrid digital twins, advancements in data synchronization, and cross-domain applications in sectors like healthcare and manufacturing. Ethical and governance considerations for large-scale digital twin adoption are also addressed, ensuring sustainable and responsible use of this technology. This research underscores the transformative potential of digital twins in real-time system monitoring while providing a roadmap to navigate current barriers and unlock future opportunities. Through the comprehensive analysis presented, this paper aims to contribute to the evolving discourse on digital twin technology, fostering its integration into modern IT ecosystems.